2011
DOI: 10.1007/s12205-011-1040-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the structural behavior of concrete filled FRP tubes with/without steel Re-bar

Abstract: This study evaluates the mechanical performance of Reinforced Concrete Filled Fiber Reinforced Tube (RCFFT) through compressive and flexural tests for the purpose of applying RCFFT as strut members for a Prestressed Concrete (PSC) Box Girder bridge. Firstly, the compressive behavior of Concrete Filled Fiber Reinforced Plastic Tube (CFFT) and RCFFT members was investigated to examine their confinement effects. Secondly, based on the experimental results, an equation for estimating the ultimate compressive stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…A number of such studies have been reported in the literature. However, the majority of these studies have been concerned with circular CFFTs (Mastrapa 1997;Saafi et al 1999;Tegola and Manni 1999;Mirmiran et al 2001;Moss 2001;Mandal et al 2005;Zhu et al 2005;Li 2006;Mohamed and Masmoudi 2010;Park et al 2011), and only a few studies have investigated the axial compressive behavior of square and rectangular CFFTs Hong and Kim 2004;Fam et al 2005;Ozbakkaloglu and Oehlers 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…A number of such studies have been reported in the literature. However, the majority of these studies have been concerned with circular CFFTs (Mastrapa 1997;Saafi et al 1999;Tegola and Manni 1999;Mirmiran et al 2001;Moss 2001;Mandal et al 2005;Zhu et al 2005;Li 2006;Mohamed and Masmoudi 2010;Park et al 2011), and only a few studies have investigated the axial compressive behavior of square and rectangular CFFTs Hong and Kim 2004;Fam et al 2005;Ozbakkaloglu and Oehlers 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies reported in the literature on the compressive behavior of CFFTs have been concerned with circular CFFTs [24][25][26][27][28][29][30][31][32][33], and only a few studies have investigated the axial compressive behavior of square and rectangular CFFTs [11][12][13][14][15][16]34].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the CFFT columns in Jolly and Lillistone (1998a), Masmoudi (2008b, 2010), Mohamed (2011), andPark et al (2011) have not been included.…”
Section: Selection Criteria Of the Cfft Databasementioning
confidence: 99%
“…It also serves as a formwork and prevents ingress of harmful chlorides and salts, and hence slows down the deterioration in the strength and ductility of concrete columns (Lillistone and Jolly 2000). The influence of different aspects of circular CFFT columns including tube thickness, diameter of the tube, tube height to diameter ratio, unconfined concrete strength, cross sectional shape, orientation of fibres, fibre type, tube manufacturing method, specimen end condition and loading (Axial, flexural and seismic) conditions on the strength and strain enhancement ratios of CFFT columns were investigated by Jolly (1997, 2000), Mastrapa (1997), Jolly and Lillistone (1998a, b), Samaan et al (1998), Matthys et al (1999), Saafi et al (1999), Tegola and Manni (1999), Rizkalla (2001a, b, 2002), Harries and Carey (2002), Hong and Kim (2004), Cole and Fam (2006), Ozbakkaloglu and Saatcioglu (2006), Li and Ou (2007), Mohamed and Masmoudi (2008a, b), Ozbakkaloglu and Oehlers (2008a), Park et al (2011), Ozbakkaloglu (2013a, Ozbakkaloglu and Vincent (2013), Idris and Ozbakkaloglu (2013), Vincent and Ozbakkaloglu (2013a, b), Hadi et al (2015Hadi et al ( , 2016.…”
Section: Introductionmentioning
confidence: 99%